2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091310
|View full text |Cite
|
Sign up to set email alerts
|

Assessing task compliance following mobile phone-based video reminders

Abstract: In the development of technology for people with mild dementia it is essential to achieve a combination of the features which provide both support and monitoring along with the ability to offer a level of personalization. Reminding support by means of personalized video reminders portraying a relative or friend combined with sensors to assess whether the requested task was performed lends itself as an ideal combination to achieve this aim. This study assesses the potential of using low cost, off the shelf sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Throughout this iterative process a range of evaluations has been undertaken with a cohort of 40 PwD and their respective caregivers. The technological platform has been updated in accordance with feedback from these evaluations [2]- [5]. The development of the MPVS system and its pretrial evaluation was reported in [2] on the design and usability of the system along with its technical stability based on nine recruited participants.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout this iterative process a range of evaluations has been undertaken with a cohort of 40 PwD and their respective caregivers. The technological platform has been updated in accordance with feedback from these evaluations [2]- [5]. The development of the MPVS system and its pretrial evaluation was reported in [2] on the design and usability of the system along with its technical stability based on nine recruited participants.…”
Section: Data Collectionmentioning
confidence: 99%
“…A longitudinal trial was subsequently carried out over a technology usage period of 5 weeks on patients with AD to assess the possibility of fully incorporating the technology into everyday life [4]. A validation study on the possibility of assessing compliance of performance of a task following reminders using low cost, off the shelf sensors was conducted in a lab-based environment with ten healthy young participants [5]. In an attempt to identify the relevant features pertaining to adoption or abandonment of the system, interviews were performed with the various members of the research and development team, which included: biomedical engineers, computer scientists, research nurses, and geriatric consultants.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Video home monitoring and reminder systems have also been tested as a means for improving compliance in cognitively impaired patients [57,58]. For example, in a cohort of 8 patients with mild dementia, those monitored using 2-way video technology demonstrated stable treatment adherence, whilst adherence in unmonitored patients decreased significantly over the treatment period [57].…”
Section: Interventions To Improve Adherence In Admentioning
confidence: 99%
“…Borenstein and Pearson (2010), quoting Oosterlaken, emphasises that the details of design are morally significant. Details such as a step-by-step design (Aarts et al, 2007;Burleson et al, 2012;Pulli et al, 2012), or large and coloured buttons (O'Neill, Parente, et al, 2011;Picking et al, 2012), and the overall intuitiveness (Maguire et al, 2011) of a system are preferred if these are helpful for the end-users. The reported difficulties of elderly users of ICT are usually about hardware issues, inconsistent interface, screen size, height mobility, information interpretation or the overall mental (rather complex) model applied (Lorenzen-Huber et al, 2011;Wallace et al, 2010).…”
Section: User Involvement In Randdmentioning
confidence: 99%